Renal hemodynamics and fatty acid uptake: effects of obesity and weight loss - Rebelos E; Dadson P; Oikonen V; Iida H; Hannukainen JC; Iozzo P; Ferrannini E; Nuutila P (AMER PHYSIOLOGICAL SOC, 2022)
Human studies of renal hemodynamics and metabolism in obesity are insufficient. We hypothesized that renal perfusion and renal free fatty acid (FFA) uptake are higher in subjects with morbid obesity compared with lean subjects and that they both decrease after bariatric surgery. Cortical and medullary hemodynamics and metabolism were measured in 23 morbidly obese women and 15 age- and sex-matched nonobese controls by PET scanning of [O-15]-H2O (perfusion) and 14(R,S)-[F-18]fluoro-6-thia-heptadecanoate (FFA uptake). Kidney volume and radiodensity were measured by computed tomography, cardiac output by MRI. Obese subjects were re-studied 6 mo after bariatric surgery. Obese subjects had higher renal volume but lower radiodensity, suggesting accumulation of water and/or lipid. Both cardiac output and estimated glomerular filtration rate (eGFR) were increased by similar to 25% in the obese. Total renal blood flow was higher in the obese [885 (317) (expressed as median and interquartile range) vs. 749 (300) (expressed as means and SD) ml/min of controls, P = 0.049]. In both groups, regional blood perfusion was higher in the cortex than medulla; in either region, FFA uptake was similar to 50% higher in the obese as a consequence of higher circulating FFA levels. Following weight loss (26 +/- 8 kg), total renal blood flow was reduced (P = 0.006). Renal volume, eGFR, cortical and medullary FFA uptake were decreased but not fully normalized. Obesity is associated with renal structural, hemodynamic, and metabolic changes. Six months after bariatric surgery, the hemodynamic changes are reversed and the structural changes are improved. On the contrary, renal FFA uptake remains increased, driven by high substrate availability.